A spiritual-based intervention in enhancing factors of well-being among older adults in home-based care. Issue 1 (2nd January 2022) - Al-Nasa'h, Mais
ABSTRACT: This study purposed to evaluate the effectiveness of group intervention (spiritual based) in decreasing depression and perceived stressors besides enhancing spiritual well-being and life satisfaction among a sample of older adults who reside in a home-based care setting. This study utilized the Geriatric Depression Scale (GDS-15), Perceived Stress Scale, Spiritual Well-being Scale, and Satisfaction with Life Scale to measure the dependent variables. Thirty participants volunteered to participate in this study through a convenience sample. The researcher randomly assigned the participants into two equal groups. The result revealed that participants in the experimental group for the spiritual intervention significantly scored higher in the posttest on the Spiritual Well-being Scale and Satisfaction with Life Scale. However, their scores significantly decreased in GDS-15 and PSS when compared with the control group.